Avaliação da biocompatibilidade do compósito biocerâmica/ácido poli (lático-co-glicólico) em fibroblastos e macrófagos e da resposta pulpar após capeamento direto - Alfonso Gala Garcia (2010)
The pulp capping with bioceramics, polymers and cements biomaterials able to trigger resident cells in the pulp to differentiate into odontoblast-like cells and to induce the formation of tertiary dentin is being investigated. The aim of the present study was to assess the cell viability of -tricalcium phosphate-hydroxyapatite bioceramic (BC) and poly (lactic-co-glycolic acid) (PLGA) composite (BC/PLGA) in peritoneal macrophages, human dental pulp fibroblasts (FP5) culture and to evaluate the rat dental pulp after direct capping pulp. The cell viability was evaluated using a MTT test in the following groups at 0, 24 and 48h for fibroblasts and 48h for macrophages. The result of cellular viability were statistically analyzed by ANOVA and supplemented by Tukey test (p > 0.05) for the 8 replicated for fibroblasts and 4 replicated for macrophages. There was progressive cell growth in all experimental groups in a similar form among the groups, although the composite presented a mild decreasing in cellullar counting been significantly lower than control after 48 h. The histological evaluation of inflammatory infiltrate and dentinal bridge formation after 60 d were carried after direct pulp capping in the groups: BC/PLGA composite; BC; PLGA and Ca(OH)2. Scores were established for the hard tissue formation, general state of pulp and inflammatory response level. In vivo study showed that after 60 d BC/PLGA composite, BC or Ca(OH)2 groups had presence of dentinal bridge been that composite was the most prevalent (90%) reached the best scores when compare with the characteristic response of Ca(OH)2 or when compare with the other groups. Mild to moderate inflammatory response was the most prevalent general state of the pulp after 30 days similar between composite (60%), or Ca(OH)2 (65%). Moreover, necrosis was more prevalent after 60 days in both groups. The results obtained of reparative dentine bridge verified after pulp capping after 60 days with the experimental materials in vivo were possibly due to the chosen model. In conclusion, the BC/PLGA composite is biocompatible with human fibroblasts and peritoneal macrophages and direct pulp capping had the best tissue response when compare with Ca(OH)2.